PENGEMBANGAN MODUL PEMBELAJARAN BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS - Riska Septia Wahyuningtyas; Familia Novita Simanjuntak (Jurnal Pro-Life, 2020)
This study aimed to develop an environmental pollution module based on local wisdom of Gunungkidul to improve the critical thinking skills of SMP / MTs students. This research was an RND (Research and Development) research. The development of this module adapted the steps of RND research according to Sugiyono (2016) which this step is potentials and problems, data collection, product design, design validation, design revision, product testing, product revision, usage trials, mass production. This first year research only covered potential problems, data collection, product design, design validation, and design revision. This module was created by placing indicators of critical thinking skills on each subject. Critical thinking indicators included providing simple explanations, building basic skills, concluding, providing further explanation, and developing strategies and tactics. Critical thinking indicators made on each subject will be able to develop students' critical thinking skills. Students' critical thinking would also develop by placing Gunungkidul's local creativity products in each module subject. The module got a very decent validation value in terms of material, media, and language. Keywords: module, critical thinking, local wisdom